Performance of Rodent Spermatozoa Over Time Is Enhanced by Increased ATP Concentrations: The Role of Sperm Competition. Issue 3 (1st September 2015) - Tourmente, Maximiliano; Villar-Moya, Pilar; Varea-Sánchez, María; Luque-Larena, Juan J.; Rial, Eduardo; Roldan, Eduardo R. S.
Abstract: Sperm viability, acrosome integrity, motility, and swimming velocity are determinants of male fertility and exhibit an extreme degree of variation among closely related species. Many of these sperm parameters are associated with sperm ATP content, which has led to predictions of trade-offs between ATP content and sperm motility and velocity. Selective pressures imposed by sperm competition have been proposed as evolutionary causes of this pattern of diversity in sperm traits. Here, we examine variation in sperm viability, acrosome integrity, motility, swimming velocity, and ATP content over time, among 18 species of closely related muroid rodents, to address the following questions: (a) Do sperm from closely related species vary in ATP content after a period of incubation? (b) Are these differences in ATP levels related to differences in other sperm traits? (c) Are differences in ATP content and sperm performance over time explained by the levels of sperm competition in these species? Our results revealed a high degree of interspecific variability in changes in sperm ATP content, acrosome integrity, sperm motility and swimming velocity over time. Additionally, species with high sperm competition levels were able to maintain higher levels of sperm motility and faster sperm swimming velocity when they were incubated under conditions that support sperm survival. Furthermore, we show that the maintenance of such levels of sperm performance is correlated with the ability of sperm to sustain high concentrations of intracellular ATP over time. Thus, sperm competition may have an important role maximizing sperm metabolism and performance and, ultimately, the fertilizing capacity of spermatozoa.